1997
DOI: 10.1063/1.473605
|View full text |Cite
|
Sign up to set email alerts
|

Surface scattering of hyperthermal (10–50 eV) neutral C60: Angular and energy distributions

Abstract: The scattering dynamics of hyperthermal C60 from a carbonized nickel surface at impact energies E0=10–50 eV was studied by high resolution angular and energy distributions. The scattered energy scales linearly with E0 and kinetic energy losses vary with scattering angle from ∼85 to ∼40%. Nearly complete decoupling between normal and tangential energy losses was found. The tangential losses are described in terms of various models of rotational excitation and the involvement of translational slip is concluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Primary beam energy distributions were corrected also for the ͑cylindrical͒ analyzer transmission as described before. 23 In former experiments 20,23 we have verified that the ionizer stage does not introduce any shift or distortion in the kinetic energy distribution of the neutrals by comparing it with time of flight measurements and by calibrating against thermal background gas and effusive beams. For each E 0 value the corresponding distributions of C 60…”
Section: Methodsmentioning
confidence: 82%
See 3 more Smart Citations
“…Primary beam energy distributions were corrected also for the ͑cylindrical͒ analyzer transmission as described before. 23 In former experiments 20,23 we have verified that the ionizer stage does not introduce any shift or distortion in the kinetic energy distribution of the neutrals by comparing it with time of flight measurements and by calibrating against thermal background gas and effusive beams. For each E 0 value the corresponding distributions of C 60…”
Section: Methodsmentioning
confidence: 82%
“…The most probable values of the corresponding distributions ͑peak values͒ will be denoted im and rm . Formerly we have found that the scattered beam energy E s scales nearly linearly with the primary beam energy E 0 and that full kinetic energy losses vary with scattering angle from ϳ85% for ϭ135°to ϳ40% for ϭ45°with nearly complete decoupling between normal and tangential energy losses 20,21 ͑for low values of E 0 one need to take into account surface barrier effects͒. For the two different scattering configurations we have observed the same energy loss of about 90%-85% from the normal component and about 25% from the tangential component.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…The fact that the I(8,) dependencies are rather narrow implies that the I (8,) and the experiment provides evidence in favor of a spherical SPB (or a very small Eb value in the case of a flat SPB) and the independence of k,, and k, from E,and Bi. Analyzing the experimental results for $ = 45" in terms of the spherical SPB model, 19 we ObtainE, = 0.9 eV, = 0.75, and kL = 0.20. The dynamically determined (scattering experiment) value of Eb = 0.9 eV is smaller than the equilibrium value (TPD experiment) of Ed = 1.8 eV by 0.9 eV.…”
Section: Kinetic Energy Losses and Angular Distributionsmentioning
confidence: 99%